Pengaruh Karakteristik Usaha dan Wirausaha Terhadap Kinerja UMKM Industri Pengolahan Perikanan di Kabupaten Sukabumi - Yusuf Iskandar; Nimmi Zulbainarni; Siti Jahroh (Universitas Tidar, 2020)
The performance of fisheries processing industry could be known through the production of processed fish and income which obtained by the entrepreneurs. Fisheries processing in Sukabumi Regency as an industry certainly has various factors that influence its performance. The purpose of this research was to analyze the effect of MSMEs and MSME actors characteristics on the performance of MSMEs in Sukabumi Regency. The research was conducted in Sukabumi Regency with the consideration that Sukabumi has superior MSME fishery processing industry products. The data used in the research were obtained from the results of interviews using the questionnaire. The number of samples used was 99 units of MSMEs which were selected by proportional cluster random sampling technique. The research data obtained were analyzed using the Structural Equation Modeling (SEM) method with the help of SmartPLS 3.2.7 software. The results showed that the characteristics of MSMEs had a positive and significant effect on the performance of MSMEs, and the characteristics of MSME actors consisting of demographic, psychological and cultural characteristics had a positive and significant effect on the performance of MSMEs. Based on these results, a psychological and cultural approach is needed for each program that will be carried out related to improving the performance of MSMEs in the fisheries processing industry in Sukabumi Regency.